Pengaruh Motivasi dan Kemampuan Kerja Terhadap Kinerja Pegawai pada Kantor Satuan Polisi Pamong Praja Kota Sibolga - Aryo Fredrick Nico Gabriel Hutagalung; Sahat Simatupang; Yusi Tri Utari Panggabean (Jurnal Publikasi Ilmu Manajemen, 2023)
Employees will show maximum performance if they have good motivation and ability to work. The formulation of the problem in this study is Do Motivation and Work Ability Have an Influence Simultaneously on Employee Performance at the Civil Service Police Unit in Sibolga City? The purpose of this study was to determine the effect of motivation and ability to work simultaneously on employee performance at the Civil Service Police Unit in Sibolga City. The hypothesis in this study is motivation and work ability to influence employees at the Civil Service Police Unit Office, Sibolga City. The type of research that the authors use is quantitative research using an associative approach. Total population of 301 people. The sample used was 25% of the population totaling 75 people. Source of data comes from primary and secondary data. Data were analyzed using descriptive analysis and quantitative analysis. Based on the research results, it is known that work motivation simultaneously has a positive effect on the performance of Civil Service Police Unit employees in Sibolga City, where Fcount (44.747) is greater than Ftable (3.13) or (44.747 > 3.13). Partially the motivation variable has the most influence on employee performance, where the t-count value is 4.056 > table value 1.993 (4.056> 1.993) or significant (Sig-t) of 0.000 <α (0.05). Partially the work ability variable has a positive and significant effect on employee performance, where the t-count value is 2.823 > table value 1.993 (2.823 > 1.993) or significant (Sig-t) of 0.006 <α (0.05). The R Square determination coefficient of 0.554 means that 55.4% of employee performance can be influenced by motivation and work ability. While the remaining 44.6% can be influenced by other factors not discussed in this study. The multiple linear regression model obtained by the regression equation is Y = 10.148 + 0.402 X1 + 0.308 X2 indicating a positive performance.